2017
DOI: 10.17957/ijab/15.0287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi and Fertilization Levels on Industrial Tomato Growth and Production

Abstract: The effect of arbuscular mycorrhizal fungi (AMF) on industrial tomato (Lycopersicon esculentum Mill. cv. Isma F1) cultivated in North-Eastern Algeria was evaluated under greenhouse and field conditions in a vertisol soil intended for the cultivation of industrial tomato. In the greenhouse, a commercial AMF inoculum and native fungal isolates consisting of Funneliformis mosseae and Septoglomus constrictum, were added in sterilized or non-sterilized soil and tested for their effects on the growth of tomato. Inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
3
14
0
6
Order By: Relevance
“…Dentre os fatores que podem influenciar na colonização micorrízica do tomateiro pode-se citar: a interação da espécie de FMA com a planta hospedeira (Ortas et al, 2013;Banla et al, 2015); o período de cultivo (Rizvi et al, 2015) e a utilização de adubos minerais e/ou orgânicos (Ziane et al, 2017).…”
Section: Crescimento E Colonização Das Mudas Do Tomateiro Ipa06 Com Iunclassified
See 2 more Smart Citations
“…Dentre os fatores que podem influenciar na colonização micorrízica do tomateiro pode-se citar: a interação da espécie de FMA com a planta hospedeira (Ortas et al, 2013;Banla et al, 2015); o período de cultivo (Rizvi et al, 2015) e a utilização de adubos minerais e/ou orgânicos (Ziane et al, 2017).…”
Section: Crescimento E Colonização Das Mudas Do Tomateiro Ipa06 Com Iunclassified
“…Rivero et al (2018) também ressaltaram que a colonização micorrízica do tomateiro favoreceu o incremento da biomassa da raiz. Assim como, Ziane et al (2017) mencionaram o aumento de 22% na altura da planta, 23% na massa fresca da parte aérea, 16% na massa fresca da raiz, 15% de massa seca da raiz do tomateiro industrial cultivado com FMA. Todavia, a colonização micorrízica não garante o incremento na biomassa da planta, tal como observado em tomateiro com FMA por Banla et al (2015).…”
Section: /9unclassified
See 1 more Smart Citation
“…In a greenhouse experiment, AM fungal inoculation with BIOCULT mycorrhiza granules (consisting of both G. etunicatum and G. intraradices) made on 'Rodade' tomatoes, exhibited superior transplant performance due to their higher shoot fresh weight, high shoot/root ratio, higher root biomass and higher root growth rate [71]. In a recent report Ziane et al envisaged the importance of AM fungi in facilitating optimal fertilizer utilization in order to achieve satisfactory growth and yield of a tomato crop [72]. Additionally, they suggested that the application of AM fungi could compensate for the reduction in chemical fertilizers, thus offering a more sustainable farming system that was respectful of the environment.…”
Section: Am Fungal Utility In Hydroponic Greenhousesmentioning
confidence: 99%
“…In return, the host plants provide the symbiotic fungus with photoassimilates for nutrition. By these interactions, the AMF promotes plant growth (SANTOS et al, 2018a); induces the defense system against pathogens and/or pests (VOLPE et al, 2018;HEIDJEN et al, 2015); increases the absorption of water and nutrients and reduce the consumption of mineral fertilizers (ZIANE et al, 2017); reducing nitrogen and phosphorus losses in the soil (TEUTSCHEROVA et al, 2019;OKONJI et al, 2018), and promoting tolerance to drought and salinity (RIVERO et al, 2018). However, the beneficial effects of AMF symbiosis on the host plant are not restricted to plant growth.…”
Section: Introductionmentioning
confidence: 99%